Analisis Penentuan Prioritas Pengembangan Unsur Pendukung Desa Wisata di Dewa Leuwilaja, Kecamatan Sindangwangi, Kabupaten Majalengka - Sri Rum Giyarsih; Evi Wulandari (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
As time goes by, the tourism sector, especially tourist villages, is increasingly developing and becoming a new star for the economy of a region. Leuwilaja Village, located in Sindangwangi District, Majalengka Regency, West Java Province, has potential local economic resources in the form of a rattan craft center which can then be developed as a rattan tourism village. The village government and community have the desire to develop a rattan tourism village as a forum for the community's economy. There needs to be a main priority program plan in developing tourist villages to make it easier for stakeholders, both the government and the community, to develop tourist villages. This analysis was prepared as a form of community service through UGM 2023 KKN-PPM activities with the aim of assisting in identifying supporting elements and strategies that can be implemented to optimize the existing potential for developing tourist villages. This analysis uses a qualitative descriptive approach with data collection methods in the form of interviews, documentation, field observations, and continued with rattan business mapping to support the results of field observations. Meanwhile, the data analysis technique used is Strength, Weakness, Opportunity, and Threat (SWOT) analysis to determine tourism village development strategies. The research results show that the tourism support elements in Leuwilaja Village, both in terms of amenities and accessibility, are quite optimal in supporting the existence of a tourist village, but institutions still need to be improved again because there is still a lack of management of tourism potential. The priority things to be developed first to support the development of tourist villages in Leuwilaja Village are developing new attractions, developing human resource skills in creating new innovations, optimizing public facilities, developing infrastructure and spatial planning, and increasing collaboration with various external parties.